2015
DOI: 10.2174/1566524015666150505161412
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations in Lung Adenocarcinoma: Molecular and Epidemiological Characteristics, Methods for Detection, and Therapeutic Strategy Perspectives

Abstract: KRAS mutations are detected in over one third of lung adenocarcinomas, most frequently in Caucasian and smoker patients. The impact of KRAS mutations on lung adenocarcinoma prognosis is currently subject to debate, as is their impact on the response to chemotherapy and EGFR tyrosine kinase inhibitors. The different methods for KRAS status assessment, based on histological and cytological samples or biological fluids, offer varying sensitivities. Since no treatments are available in clinical routine for KRAS-mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…The frequency of KRAS -mutant (34%) and EGFR -mutant (12.5%) tumors was indeed similar that observed in other Caucasian populations of advanced NSCLC patients [20,21]. Furthermore, we analyzed data not only from patients enrolled in clinical trials, but also from all patients diagnosed in routine practice.…”
Section: Discussionsupporting
confidence: 71%
“…The frequency of KRAS -mutant (34%) and EGFR -mutant (12.5%) tumors was indeed similar that observed in other Caucasian populations of advanced NSCLC patients [20,21]. Furthermore, we analyzed data not only from patients enrolled in clinical trials, but also from all patients diagnosed in routine practice.…”
Section: Discussionsupporting
confidence: 71%
“…For example, Bournet et al (31) reported that KRAS G12D mutant was an independent prognostic factor for unresectable pancreatic cancer. It had been proposed that in non-small cell lung cancer, the G12D mutation subtype was associated with the activation of the phosphoinositide 3-kinase/AKT serine/threonine kinase (AKT) and MEK signaling whereas mutation G12V or G12C preferred to activate Raf and Ral, and decreased growth factor-dependent AKT activation (32,33). These findings led to the present study in which the association between signaling pathways and the role of KRAS mutation subtypes on prognosis of patients with CRC were investigated, particularly in patients with mCRC from different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic alterations are promising molecular targets as ROS1 or RET rearrangements or BRAF , PIK3CA, C-MET and HER2 mutations 4–8. Other biomarkers as KRAS mutations are associated with a poor prognosis but do not allow targeted therapies to date with nevertheless some recent encouraging results in this field 9 10. Driver genetics alterations are mostly mutually exclusive and, besides EGFR and ALK testing recommended in international guidelines, a rapid KRAS assay may be performed initially as a help to exclude KRAS -mutated tumours from EGFR mutation testing as a part of an algorithm designed to maximise testing efficiency 11 12…”
Section: Introductionmentioning
confidence: 99%